Immunoglobulins in recurrent pregnancy loss: Emerging biomarkers and therapeutic targets - Umme Kulsum; K. S. Praveen Kumar; Pallavi Shekar; C. Kamala; Naidu M. Swati Krishnaswami; Ananya Hegde; Lakshitha V. Jayakrishna; Meghana Hangala Shivakumaraswamy; Akila Prashant (Molecular Biology Reports, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disorder that affects approximately 1–5% of couples of reproductive age and is associated with considerable emotional and clinical burden. Although several genetic, anatomical, endocrine, infectious, and thrombophilic factors have been implicated, the underlying cause remains unexplained in nearly half of all cases, highlighting the importance of immune dysregulation in disease pathogenesis. Among immune factors, immunoglobulins play pivotal roles in maintaining maternal–fetal immune homeostasis by regulating immune tolerance, complement activation, autoantibody production, and inflammatory signalling. However, dysregulated humoral immune responses may disrupt placental development and fetal tolerance, thereby contributing to pregnancy failure. This review summarises current evidence regarding the biological functions of immunoglobulins in normal pregnancy and their involvement in the pathogenesis of RPL. We discuss the clinical significance of immunoglobulin-associated biomarkers, including antiphospholipid, antinuclear, anti-thyroid, and other pregnancy-related autoantibodies, and evaluate their utility in risk stratification and diagnosis. Emerging immunoglobulin-based therapeutic strategies, particularly intravenous immunoglobulin (IVIG), are reviewed in the context of current clinical evidence and guideline recommendations. Finally, we highlight the potential of comprehensive immunoglobulin profiling, integrated with clinical and molecular biomarkers, to support precision medicine approaches for individualised diagnosis, prognosis, and therapeutic decision-making in women with RPL. Continued mechanistic and translational research will be essential to validate these biomarkers and optimise personalised immunomodulatory interventions for improving pregnancy outcomes.